The School Research Lead / Tom Bennett. - Bennett, Tom (Distributed by ERIC Clearinghouse, 2015)
The researchED movement has generated a new debate about the role of research in schools. Of course there have always been teachers interested in undertaking research and applying the research findings of others. However, involvement in research has tended to be the personal enthusiasm of the individual teacher rather than a coordinated whole school endeavour. One of the many exciting aspects of the current debate that researchED has stimulated is the emergence of the idea of the Research Lead. Many schools now have a key individual who takes a whole school view of the use of evidence. So how should new Research Leads see their role? This report addresses the question in two ways. Tom Bennett, the founder of researchED, has written this thought-provoking essay that sets out some of the ways in which the work of the Research Lead can be conceptualised. He explores a range of different approaches to research leadership. In addition to his tour of the horizon, several pioneering Research Leads have provided fascinating case studies of research leadership in action in their own schools. Both his analysis and the vignettes from the schools collectively make a powerful case for the new role and the potential benefits in terms of better teaching and learning. The different contributions also make it clear that there is no single blueprint that schools should follow as they explore research engagement. The author provides a deliberately diverse set of possible interpretations of research leadership. The unifying factor that is present in all of his approaches is a strong sense of research as a collective and collegiate endeavour. Similarly the case studies, while illustrating different styles of research leadership, are linked by a shared view of the school as a professional learning community. This is an important and timely report. Our understanding of teacher professionalism is in flux and we have a chance to re-define teaching as a research-engaged calling. The new cadre of Research Leads can influence this and make sure that our view of evidence is securely institutional rather than individualistic. [Introduction by Tony McAleavy. For the first report in this series, see ED574403. For the third report in this series, see ED574405.]